Vulnerabilities of homeless women: social markers of gender and race/color - Keila Cristina Costa Barros; Rita de Cássia Rocha Moreira; Jeane Freitas de Oliveira; Daine Ferreira Brazil do Nascimento; Marília Emanuela Ferreira de Jesus; Ricardo Bruno Santos Ferreira (Universidade Federal do Ceará, 2022)
Objective: to unveil the vulnerabilities of homeless women linked to the social markers of gender and race/color. Methods: qualitative study, developed with ten homeless women through participant observation, field diary, and sociodemographic questionnaire, systematized based on content analysis. Results: it was found that gender identity and race/color act as potentiators of the situation of vulnerability of women. It is believed that structural racism and machismo feed back into the streets and perpetuate themselves in a perverse cycle of denial of women's rights, which is potentiated by the omission of the State and extensive social and economic inequality. Conclusion: gender and race/color potentiate the vulnerabilities of homeless women that intersect precarious social conditions, denial of rights, and favor illness. Contributions to practice: to present information that enables reflections and creation of care strategies for homeless women, understood in their singularities.